Pengaruh Model Pembelajaran Blended Learning Terhadap Hasil Belajar Siswa Kelas V SDN Sedati Gede II - Fanani Bagasworo; Rarasaning Satianingsih; Cholifah Tur Rosidah (LPPM Universitas PGRI Adi Buana, 2022)
Education is an influence on civilization, both economic and social, so that in the learning or educational process, interaction between students and teachers is needed. Based on observations made, it is known that the achievement of student learning outcomes has been relatively unstable due to the constraints of the Covid-19. This study aims to determine the effect of blended learning based on google classroom on the learning outcomes of fifth grade students at Sedati Gede State Elementary School II. This study is an experimental quantitative study using observation, documentation, and test methods. And the data analysis technique used is using the percentage formula, as well as prerequisite tests, namely normality test and homogeneity test, and t test in knowing student learning outcomes. With this research, researchers can determine the effect of blended learning based on google classroom on student learning outcomes in class V Sedati Gede State Elementary School II theme 4 sub-theme 2 learning 1. The results of this study are learning outcomes using a blended learning model based on google classroom rather than using a learning model online. Thus, the use of Google Classroom-based blended learning in the new normal is more effective for education to be more varied.